Characterization of homofermentative lactobacilli isolated from kefir grains: potential use as probiotic - Golowczyc, Marina Alejandra (2008)
Considering that several health promoting properties are associated with kefir consumption anda reliable probiotic product requires a complete identification of the bacterial species, thepresent work evaluates several proved markers of probiotic potential of eleven isolates ofhomofermentative lactobacilli isolated from kefir grains and molecular identification andgenotypic diversity. Using restriction analysis of amplified ribosomal DNA (ARDRA) andanalysis of the 16S–23S rRNA internal spacer region we confirmed that all homofermentativelactobacilli belong to the species Lactobacillus plantarum. RAPD-PCR analysis allowed thediscrimination of lactobacilli in five clusters. All isolates exhibited high resistance to bile salt.High survival after one hour of exposure to pH 2.5 was observed in Lb. plantarum CIDCA8313, 83210, 8327 and 8338. All isolates were hydrophilic and non autoaggregative. IsolateCIDCA 8337 showed the highest percentage of adhesion among strains. All tested lactobacillihad strong inhibitory power against Salmonella typhimurium and Escherichia coli. Seven out ofeleven isolates showed inhibition against Sal. enterica and five isolates were effective againstSal. gallinarum. Only CIDCA 8323 and CIDCA 8327 were able to inhibit Sal. sonnei. We didnot find any correlation between the five clusters based on RAPD-PCR and the probioticproperties, suggesting that these isolates have unique characteristics.